Eventual stability and eventual boundedness for impulsive differential equations with “supremum” - Stamova, Ivanka (Mathematical Modelling and Analysis, 2011)
Eventual stability and eventual boundedness for nonlinear impulsive differential equations with supremums are studied. The impulses take place at fixed moments of time. Piecewise continuous Lyapunov functions have been applied. Method of Razumikhin as well as comparison method for scalar impulsive ordinary differential equations have been employed.